Pengaruh Kepuasan Transaksi Online Shopping dan Kepercayaan Konsumen Terhadap Sikap Konsumen E-commerce (Studi Kasus: Pembelian Produk Shopee.co.id pada Karyawan Borma Toserba Bandung) - Wala Erpurini; Wapa Samrotul Janah (Jurnal EMT KITA, 2022)
This research is meant to determine the effect of online shopping transaction satisfaction and trust on consumer attitudes in E-commerce. The population in this study were employees of Borma Toserba Bandung. The sampling technique used is the census technique because the population is not larger than 100 respondents. Data obtained from the distribution of questionnaires with a total of 56 respondents obtained from employees of borma department store bandung. The analytical method used in this research is descriptive method, and statistical analysis using multiple linear regression analysis, and hypothesis testing using t-test and f-test with a significant level of 5%. The results show that online shopping transaction satisfaction has a significant and positive effect on consumer attitudes in E-commerce, consumer trust has a significant and positive effect on consumer attitudes in E-commerce, and online shopping transaction satisfaction and consumer trust together have a significant and significant effect on consumer attitudes.